(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2016)
This essay aims to unveil the structural limits of trauma theory through a cross-cultural dialogue. It suggests the need to disarticulate the trauma paradigm as the sole episteme that shapes the question of human suffering and hopes to enrich it by providing ethical alternatives found in Chinese antiquity.